Measuring Knowledge Workers’ Productivity in the Kingdom of Saudi Arabia Telecom Industry - Jones, AbdulHafiz Henry James; Alshammari, Dr. Hammad Khammes (Archives of Business Research, 2017)
This study establishes and tests a framework for measuring knowledge workers’ output in the Kingdom of Saudi Arabia (KSA) telecom industry based on the examination of capitalized labor and average revenue per user (ARPU) to measure value added intellectual coefficient (VAIC). Quarterly financial statements from 2008-2015 were used to measure an ARPU composite score of the only four publicly traded telecommunication companies on the Saudi Exchange (Tawadul). The four telecom companies comprise 32 cases which satisfied the required number of cases needed to detect a R2 that is 50% or higher 80% of the time. A hierarchical regression was performed to measure capitalized labor (CLE), Pulic’s VAIC, and its determinants’ effects on ARPU composite score. The results showed a direct relationship between VAIC, its determinants, and ARPU composite score. The full model explained 78% of the ARPU composite score. CLE and CEE were significant with a combined R2 of 29%. This study shows how ARPU is linked to functional-level strategies in telecom industry, and can be used as a KPI to measure the productivity of knowledge workers.